Acoustic detection of bottlenose dolphin depredation on nets and implications for conservation. Issue 2 (18th December 2022) - La Manna, G.; Arrostuto, N.; Campisi, S. S.; Manghi, M.; Fois, N.; Ceccherelli, G.
Abstract: Understanding the depredation process is pivotal to the management of conflicts between wildlife and human activities. Depredation by marine mammals on fisheries occurs when animals 'steal' fish from the fishing gear, causing catch loss and damage to gear and catches. The common bottlenose dolphin is a vulnerable species and is the main depredator of coastal static net fisheries in the Mediterranean Sea. The nature and extent of the phenomenon is still poorly understood since evidence is often incomplete or inconsistent mostly due to the different methods used to measure depredation. Here, passive acoustic monitoring devices were used to estimate the consistency between dolphin acoustic detection in proximity to the net and direct dolphin observations and catch measurements at different sites in Sardinia (north‐western Mediterranean Sea). Further, some factors influencing depredation (fishing duration and fishing net length) and changes in catch amount and composition were evaluated. The frequency of dolphin detection based on direct dolphin observations was significantly lower than that based on acoustic monitoring; the latter was related to the amount of catch. Thus, the measurement of catch was more realistically related to depredation than direct dolphin observations. Further, dolphin depredation was related to the duration of the fishing operation. The measure of depredation and catch loss provided here can be used to realistically estimate the damage suffered by fishers and provide preliminary insights to guide the development of an approach for sustainable coexistence between dolphins and fisheries.